Rafael Bonilla Cerezo, José Ramón Trujillo y Begoña Rodríguez (eds.). Novela corta y teatro en el Barroco español (1613 -1685) - Hernández González, Laura (BOLETÍN DE LA BIBLIOTECA DE MENÉNDEZ PELAYO, 2013)
.